The impact of Ramadan fasting on oxidative stress levels in the second trimester of pregnancy - Esin Kasap; Raziye Torun; Sema Kardeşler; Gökşen Görgülü; M. Bora Bozgeyik; Yılmaz Güzel; Ebru Şahin Güleç (Taylor & Francis Group, 2024)
Background The primary objective of this study was to assess the effect of fasting during Ramadan on maternal oxidative stress levels and foetal development; pregnant women with uncomplicated, singleton pregnancies in the second trimester.Methods During the month of Ramadan, 23 March 2023 to 20 April 2023, 50 fasting and 50 non-fasting healthy pregnant women were enrolled in this prospective study. The fasting hours were about 14 h per day in that season. Pregnant women in the second trimester were enrolled in the study. Total antioxidant status (TAS), total oxidant status (TOS) and the oxidative stress index (OSI) were measured from maternal serum samples taken on a fasting day at the end of Ramadan. To evaluate the impact of Ramadan on the foetus, Doppler ultrasonography was performed in the beginning and then at the end of Ramadan in all participants and was used for the following measurements: Increase of biparietal diameter, femur length, estimated foetal body weight, amniotic fluid index and umbilical artery systolic/diastolic ratio. To discern differences between distinct cohorts, independent t-tests and Mann-Whitney's U-tests were employed based on the data distribution. A p value threshold of less than .05 was established to determine statistical significance.Results TAS level was found to be significantly lower in the group that fasted for more than 15 days compared to the non-fasting group that did not fast (p = .003), but no significant differences were found between the groups in terms of TOS and OSI (p < .05). Obstetric ultrasound parameters showed no significant differences between the two groups (p < .05).Conclusions The present study suggests that fasting during the second trimester of pregnancy does not substantially impact maternal or foetal health, as indicated by most oxidative stress markers and foetal parameters studied. However, the observed reduction in the TAS levels in the fasting group warrants further investigation.